RECOMPOSIÇÃO DA APRENDIZAGEM ESCOLAR DE ESTUDANTES DA EDUCAÇÃO BÁSICA COM TRANSTORNO DO ESPECTRO AUTISTA - ISABELLE DA CRUZ FERNANDES (2024)
The contributions coming from the Historical-Cultural perspective to the educational field are numerous for different fields and themes, such as the approach to the inclusion of students with disabilities, with Vygotsky as the greatest exponent. He highlights that the social context cannot be simplified to one mere deduction of the individual aspect, but rather, through interactions with other individuals that the subject forges a process of humanization, therefore, based on the historical-dialectic materialist perspective. This perspective transcends the dichotomous, biologizing, naturalistic and, at times, pathological view of childhood and adolescence, exploring compensatory paths of possibilities. Considering this premise, this dissertation aims to analyze the conceptions and implementations of Learning Recomposition processes in the period after the pandemic focused on students with Autism Spectrum Disorder (ASD) enrolled in the initial grades of Elementary School. To achieve this objective, exploratory research was carried out, which was analytically divided into three other methodological processes: Bibliographic Survey; Integrative Literature Review; and exploratory and documentary research anchored in the Historical-Cultural perspective. The results made it possible to identify that the educational gaps and challenges arising from the Covid-19 pandemic did not affect everyone equally, being more harmful depending on the geographic location, financial and human resources, and the educational needs of each student. In this sense, Learning Recomposition appears as a systemic initiative seeking to reduce or fill these gaps. However, when analyzing official documents such as the Learning Recomposition Guide and the Mato Grosso do Sul Learning Recomposition Plan, as well as other proposals and research, it is clear that these documents and the methodological propositions presented in them undergo different interpretations in relation to the term and its applications. They are often perceived as school reinforcement, configuring itself as a specific action, rather than a comprehensive set of actions. Furthermore, they do not suggest or present actions related to the field of Special Education, nor do they address other contextual specificities, contradicting the proposal to Recompose learning for students when returning to classes. This situation becomes more acute when it comes to students who have Autism Spectrum Disorder.